PEMANFAATAN EKSTRAK AIR BUAH Flacourtia inermis Roxb. (LOBI-LOBI) SEBAGAI PENGAWET IKAN LAUT - Ade Pribadi; Nurhamidah Nurhamidah; Elvinawati Elvinawati (ALOTROP, 2018)
[THE  UTILIZATION OF   Flacourtia inermis Roxb. (LOB-LOBI ) FRUIT WATER EXTRACTS AS A MARINE FISH PRESERVATIVE] This research aims to determine the magnitude of the concentration and the length of time the optimum soaking water extracts of fruit Flacourtia inermis Roxb. (lobi-lobi ) as well as measuring its potential for use as a preservative in marine fish. Sample marine fish used is Kerapu Macan (Epinephelus fuscogultatus). The concentration of water extract from the fruit of F.inermis Roxb  is at levels at 10, 20, 30 and 40% with soaking time each at 1, 2 and 3 hours for any variation of the concentration. Observation of the level of the fish freshness is done with a variety of storage time of 12, 18, and 24 hours at room temperature to any variation of the concentration of extract and soaking time. The parameters used in determining the level of the freshness of the sample fish is a rate of Total Volatile Bases (TVB), moisture content, and pH. The results of the research done indicate that extracts water from the fruit of F.inermis Roxb L are potential for use as a preservative of marine fish based on the values of pH and the levels of TVB. The most optimum concentration and soaking time in Kerapu Macan fish preserve during its storage was soaking with a concentration of 30% for 1 hour, i.e., able to withstand the pace of the decline of the quality of the Kerapu Macan sample for 18 hours at room temperature: with the pH 6.7 and fish TVBvalue at 29.4 mgN/100 g.